Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1001/jamanetworkopen.2020.29256
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Outcomes Among Women With and Without Severe Acute Respiratory Syndrome Coronavirus 2 Infection

Abstract: IMPORTANCE Published data suggest that there are increased hospitalizations, placental abnormalities, and rare neonatal transmission among pregnant women with coronavirus disease 2019 (COVID-19). OBJECTIVES To evaluate adverse outcomes associated with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in pregnancy and to describe clinical management, disease progression, hospital admission, placental abnormalities, and neonatal outcomes. DESIGN, SETTING, AND PARTICIPANTS This observational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
201
4
13

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 220 publications
(274 citation statements)
references
References 17 publications
22
201
4
13
Order By: Relevance
“…However, in a large, single-institution cohort study, 95% maternal infection at an initial presentation was asymptomatic or mild. SARS-CoV-2 infection during pregnancy was not associated with adverse pregnancy outcomes ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, in a large, single-institution cohort study, 95% maternal infection at an initial presentation was asymptomatic or mild. SARS-CoV-2 infection during pregnancy was not associated with adverse pregnancy outcomes ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently Adhikari et al 7 performed a retrospective cohort study of pregnant patients delivering at a single academic center and found no association between COVID-19 and a composite adverse perinatal outcome of preterm birth, preeclampsia with severe features, or cesarean birth. However, 95% of the cohort had asymptomatic or mild disease, and it remains unknown whether perinatal outcomes differ by COVID-19 severity.…”
mentioning
confidence: 99%
“…Early reports from the UK and the USA suggest there is no risk to either, however these are based on small numbers. 25 26 Given the unknown risk to both parties, although pregnancy is not considered as a risk factor in its own right, we would recommend all people who are pregnant be regarded as high risk and offered the option to shield.…”
Section: Resultsmentioning
confidence: 99%